Ethnobotanical knowledge and conservation practices of indigenous people of Mbeliling Forest Area, Indonesia - Marlinda Mulu; ZEPHISIUS R.E. NTELOK; PETRUS SII; HILDEGARDIS MULU (Society for Indonesian Biodiversity, 2020)
Abstract. Mulu M, Ntelok ZRE, SII P, Mulu H. 2020. Ethnobotanical knowledge and conservation practices of indigenous people of Mbeliling Forest Area, Indonesia. Biodiversitas 21: 1861-1873. The indigenous people of Mbeliling Forest Area, Indonesia have long interacted with nature, in the form of utilizing forest resources for their survival. Therefore it is essential to identify the plants used to support their lives. In addition, they also have traditional institutions that manage the lives within groups. It is necessary to study the forms of environmental conservation applied by the indigenous people. This research is qualitative research with an ethnographic method and case studies. The research data is collected through observation and interviews. The data were analyzed descriptively and qualitatively. The results showed that total of 158 plant species belonging to126 genera and 64 families are used in the study area. They include 26 species used for food, 6 species for drinks, 60 species for medicine, 38 species for construction, 26 species for craft, 8 species for coloring, 6 species for cosmetics, 7 species for pesticides, and 16 species for traditional rituals. In terms of conservation, indigenous people work together with the village government. The forest area is divided into ulayat forests (communal forest) and protected forests. The management of communal forests is the right of indigenous people so that it functions as a production forest. Although communal forests are the right of indigenous people, which is managed by customary leaders, its utilization is affected by the status of protected forests established by the government. In protected forests, there are no plantations or agricultural activities.